A discussion paper on valuations for mortgage and the level of house prices. Issue 1 (2nd March 2015) - Bowcock, Philip
Abstract : Purpose: – The aim of the present paper is to consider the effect of the current approach to valuations for mortgage on the level of house prices during the housing bubble of 2000-2008 which has been a major contributor to the following recession followed previous smaller bubbles in 1972 and 1990. Despite a warning from the International Monetary Fund in 2004 that prices were too high and home buyers should "exercise particular caution", no fundamental research appears to have been done into the contribution to this of those responsible for valuation for mortgage. Design/methodology/approach: – Data from the Nationwide Quarterly Index were used as a basis and compared with the writer's professional experience in carrying out valuations for mortgage. Findings: – Instructions to valuers advising on the properties offered as security for a mortgage loan have requested only a valuation based on the market as it existed at the time of the valuation without regard to the possibility that a change in economic circumstances could cause a fall in the value of the security. Many mortgagors have found on sale or repossession that their liability to repay their mortgage is greater than the value of the property. Originality/value: – Valuations for mortgage should include an indication of the possible risks involved, including the results of changes in the global economic environment.